The Effectiveness of Blended and Printed Learning Resources in Improving Science Learning Outcomes of Student Teachers at a Distance University - Budiastra, A.A. Ketut (Advances in Social Sciences Research Journal, 2020)
Learning resources are an essential factor that determines learning outcomes, especially elementary school teacher education program students in distance education. This study aims to compare the effectiveness of blended learning and printed learning resources in improving science learning outcomes for distance education students. This study is a true experiment conducted at the Universitas Terbuka (UT) regional office of Jember, as a representation of the East Java region. Respondents of the study were 56 students using blended learning resources and 60 students using printed learning resources. The data were collected using a test of student learning outcomes and analyzed using t-test and N-gain. The results show that both blended learning and printed learning resources significantly improved learning outcomes at α = 5%, each with an average N-gain having relatively the same products at moderate levels. This study also raises information that blended learning resources are more effective than printed learning resources. This study implies that blended learning resources can be used as an innovative solution to improve student learning outcomes in distance education systems.